Isolation and Molecular Identification of proteus mirabilis isolated from hospitals in the capital Baghdad - Mohammed Kaittan Abed1 , Hasanain Khaleel Shareef2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Proteus mirabilis a Gram-negative bacteria belonging the Enterobacteriaceae family and that causes severalinfections to patients such as urinary tract infections, middle ear infections, wounds and burns, in additionto other infections. This study aimed to isolate and diagnose Proteus mirabilis bacteria collected fromdifferent samples of infection sources from patients present in many hospitals using traditional diagnosticlike morphological and biochemical tests as well as molecular methods. The Identification system for Gramnegative bacteria GN24 KIT had used to detect Proteus mirabilis species . The results of using this kit wereconfirmed by the molecular diagnosis of bacteria through the PCR technique of the 16S rRNA gene, wherethe confirmation rate was 100%. The PCR sample was analyzed in Macrogen Corporation–Korea for Sangersequencing using ABI3730XL, an automated DNA sequences. the findings were obtained and analyzed viagenius software in order to Synthesis of the phylogenetic tree of the isolated strains that resulted from thediscovery of a new global strain of Proteus mirabilis bacteria and was recorded in NCBI genebank withaccession number (MN 700085) and name (M.K.84 ).